If you really want to change the world : a guide to creating, building, and sustaining breakthrough ventures - Kressel, Henry; Winarsky, Norman, 1947- (Boston, Massachusetts : Harvard Business Review Press, 2015)
"Silicon Valley's popular approach to creating new ventures is rooted in trial and error-test markets with new concepts and a minimum amount of capital, and hope for valuable businesses to emerge. But this fail-fast, hit-or-miss, step-and-pivot, or tech-first philosophy can leave a trail of destruction and loss in its wake. It can be like a random walk in the forest-without a compass. This book is about helping the great entrepreneurs find true north. Henry Kressel and Norman Winarsky-technologists, inventors, and investors with stellar track records-have an approach for those who wish to create a market-leading company that will make an impact on the world: a disciplined and staged approach they've used to launch, invest in, and develop dozens of successful companies-and to create whole new markets. The method they describe takes the entrepreneur by the hand, step-by-step, through the critical stages of development of a great venture, from concept to acquisition or public offering, to being a mature company seeking to maintain its culture of innovation. It is a guide by innovators and for innovators, with approaches that are timeless. If You Really Want to Change the World is your guide to creating massively successful ventures. Drawing on the authors' experiences as well as those of their partners from around the world, Kressel and Winarsky share the stories of their triumphs and misses as of a way of demonstrating their method and inspiring their readers. They guide entrepreneurs and innovators in companies of all scale-start-ups, research institutions, government agencies, and corporations-on how to execute with the aim of creating companies that can change the world. "--
Tặng
Keywords: Entrepreneurship; New business enterprises; Venture capital; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Management